Effect of structural variation in the promoter region of RsMYB1.1 on the skin color of radish taproot - Kim, Jiin; Jang, Hoyeol; Huh, Sun Mi; Cho, Ara; Yim, Bomi; Jeong, Seung-Hoon; Kim, Haneul; Yu, Hee-Ju; Mun, Jeong-Hwan (Frontiers in Plant Science, 2024)
Accumulation of anthocyanins in the taproot of radish is an agronomic trait beneficial for human health.Several genetic loci are related to a red skin or flesh color of radish, however, the functional divergence of candidate genes between non-red and red radishes has not been investigated. Here, we report that a novel genetic locus on the R2 chromosome, where RsMYB1.1 is located, is associated with the red color of the skin of radish taproot. A genome-wide association study (GWAS) of 66 non-red-skinned (nR) and 34 red-skinned (R) radish accessions identified three nonsynonymous single nucleotide polymorphisms (SNPs) in the third exon of RsMYB1.1. Although the genotypes of SNP loci differed between the nR and R radishes, no functional difference in the RsMYB1.1 proteins of nR and R radishes in their physical interaction with RsTT8 was detected by yeast-two hybrid assay or in anthocyanin accumulation in tobacco and radish leaves coexpressing RsMYB1.1 and RsTT8. By contrast, insertion-or deletion-based GWAS revealed that one large AT-rich low-complexity sequence of 1.3-2 kb was inserted in the promoter region of RsMYB1.1 in the nR radishes (RsMYB1.1 nR ), whereas the R radishes had no such insertion; this represents a presence/absence variation (PAV). This insertion sequence (RsIS) was radish specific and distributed among the nine chromosomes of Raphanus genomes. Despite the extremely low transcription level of RsMYB1.1 nR in the nR radishes, the inactive RsMYB1.1 nR promoter could be functionally restored by deletion of the RsIS. The results of a transient expression assay using radish root sections suggested that the RsIS negatively regulates the expression of RsMYB1.1 nR , resulting in the downregulation of anthocyanin biosynthesis genes, including RsCHS, RsDFR, and RsANS, in the nR radishes. This work provides the first evidence of the involvement of PAV in an agronomic trait of radish.